Experimental Study on Heat and Mass Transfer Characteristics of Hollow Fiber Membrane-based Liquid Desiccant Air Dehumidification - Yin Shaoyou; Zhang Ning (Zhileng xuebao)
In the hollow-fiber-membrane-based liquid desiccant air dehumidification process, water vapor can permeate through the membrane effectively, while the liquid desiccant droplets are prevented from crossover. Hence, the traditional problems of desiccant droplet crossover and indoor environmental pollution are solved. In this research, a test rig of the membrane module is built, and the performance of the system is investigated experimentally. The results show that the dehumidification efficiency is in the range of 20%–60%. This is comparable to a direct-contact packed bed dehumidifier. The largest dehumidification rate is about 800 g/h under very hot and humid weather conditions. Moreover, the cooling capacity of the dehumidification is as high as 700 W. Therefore, it performs well even under hot, and humid South China weather conditions.